A comparative study of the TCu 380A versus TCu 200 IUDs in Nepal - Mahodadhi Shrestha; Caroline Hurst; Gaston Farr; Ramesh Amatya; Beverly Tucker; James McMaham (Asia-Pacific Population Journal, 1995)
The cost-effectiveness and proven contraceptive efficacy of the TCu 380A should be considered when selecting a long-term, safe and effective, but reversible method.